Tp‐e Interval, Tp‐e/QTc Ratio, and Fragmented QRS Are Correlated with the Severity of Liver Cirrhosis - Akboga, Mehmet Kadri (Ann Noninvasive Electrocardiol, 2016)
BACKGROUND: Arrhythmias and electrocardiographic changes are reported in several noncardiac diseases, including liver cirrhosis (LC). We intended to evaluate the interval from the peak to the end of the electrocardiographic T wave (Tp‐e), Tp‐e/QTc ratio, and fQRS as presumed markers of arrhythmias in LC. METHODS: In this cross‐sectional study, a total of 88 consecutive patients with LC according to clinical, biological, ultrasonographic, or histological criteria and 73 control subjects were enrolled. The severity of cirrhosis was classified according to Pugh‐Child's classification and Model for End‐Stage Liver Disease (MELD) score. Tp‐e interval, Tp‐e/QTc ratio, and fQRS rates were measured from the 12‐lead electrocardiogram. RESULTS: Tp‐e interval, Tp‐e/QTc ratio and fQRS rates were significantly increased in parallel to the severity of LC (P < 0.001, P < 0.001, and P = 0.003, respectively). In correlation analysis, Pugh‐Child stage showed a significantly positive correlation with Tp‐e interval (r = 0.462, P < 0.001), QTc interval (r = 0.373, P < 0.001), Tp‐e/QTc ratio (r = 0.352, P < 0.001), and fQRS (r = 0.407, P < 0.001). Furthermore, Tp‐e interval (r = 0.414, P < 0.001) and Tp‐e/QTc ratio (r = 0.426, P< 0.001) had significant positive correlation with MELD score. CONCLUSIONS: Our study demonstrated that Tp‐e interval, Tp‐e/QTc ratios, and fQRS rates were significantly increased in parallel to the severity of LC. Thus, these findings may implicate that Tp‐e interval, Tp‐e/QTc ratio, and fQRS may be novel and useful indicators for prediction of arrhythmias in LC.